Responses of Four Rice Varieties to Elevated CO2 and Different Salinity Levels - Sheidollah Kazemi; Hamid Reza Eshghizadeh; Morteza Zahedi (Rice Science, 2018)
Abstract:: This study was carried out in 2014 at Isfahan University of Technology, Iran, to evaluate the responses of four rice varieties (Neda, Deylamani, Shiroudi and Domsorkh) to ambient (360 ± 50 μmol/mol) and elevated (700 ± 50 μmol/mol) air carbon dioxide (CO2) concentrations under four salinity levels (0, 30, 60 and 90 mmol/L NaCl). There was significant variation among rice varieties in response to elevated CO2 concentration under the four salinity levels. Under non-saline condition, elevated CO2 increased the dry weight of Neda, Deylamani and Domsorkh by 8%, 50% and 8%, respectively, but reversely decreased that of Shiroudi by 34%. Increasing CO2 concentration significantly reduced the negative effects of salinity on Shiroudi, but these effects were even increased in Deylamani and Domsorkh under all the salinity levels and in Neda only under 30 and 60 mmol/L NaCl. Significant correlations were established between plant dry weight, SPAD value and leaf area under both CO2 levels. However, this trend was observed only at ambient CO2 concentration in the presence of soluble carbohydrates. The results revealed the genotype and salinity dependence of the effects of CO2 concentrations on the rice traits investigated. Key words: CO2 concentration, genetic diversity, salt tolerance, water soluble carbohydrate